Correlation between Bone Scan Findings and CA 153 in Patients with Carcinoma Breast (Bangladesh Journal of Nuclear Medicine, 2018)
Objectives: Breast carcinoma is the most life threatening malignant condition in women. This malignant disease commonly metastasizes to bone. Carbohydrate antigen (CA) 15-3 is a circulating human breast cancer associated antigen used as a tumor marker in the screening of breast cancer patients for metastasis. The objective of this study was to compare the levels of CA 15-3 and bone scan findings in patients with breast cancer.Patients and Methods: This cross sectional study was carried out at Institute of Nuclear Medicine and Allied sciences, Mitford, Dhaka, from January 2015 to December 2015. A total of 75 diagnosed breast cancer patients were enrolled in this study. All of them underwent bone scan. The tumor maker CA 15-3 was compared with bone scan findings. Pearson’s correlation coefficient test was done to see the relationship between bone scan and CA 15-3.Results: Mean age of the patients was 47.60 ± 10.53 years (range 25 to 65 years). About half (49%) of the patients belong to the age group 50 years and above. Mean ± SD of CA 15-3 was 84.06 ± 104.60 U/ml (range from 10.12 to 395.30 U/ml). Out of 75 patients, 33 patients showed elevated CA 15-3 level, among them 42% had negative bone scan with mean ± SD CA 15-3 level 60.98 ± 9.95 U/ml (range 40.26-72.17 U/ml), 58% patients had positive bone scan with mean ± SD CA 15-3 level 246.23 ± 81.35U/ml (range 110-395.30 U/ml). CA 15-3 was within normal limit (range 10.20-30.10 U/ml) in 42 patients. Among them 29% patients had negative bone scan and 71% patients had positive bone scan. Pearson’s correlation coefficient test showed positive relationship (p = 0.001, r = 0.343) between CA 15-3 level and bone scan findings.Conclusion: The result of the study showed positive relationship between the bone scan findings and CA 15-3 level of carcinoma breast patients.Bangladesh J. Nuclear Med. 20(1): 24-26, January 2017